Analysis of risk factors for surgical site infection: A case research in an Orthopedic Hospital (Healthcare Industry) - Bhalaji, R. K. A.; Bathrinath, S.; Ponnambalam, S. G.; Saravanasankar, S. (Penerbit UMP, 2019)
This study portrays a ranked structure on different risk factors including patient, surgery and hospital related risk factors and allied unfavorable outcomes concerning an orthopedic hospital. The paper suggests a methodical surgical site infection (SSI) risk assessment method for assessing level of risk factors using three vital quantifying elements; outcome, time and likelihood of exposure. To transform the linguistic data into numeric risk scores, an enhanced decision making technique using fuzzy set theory has been endeavored in this paper. The notion of ‘centre of area’ technique for widespread TFNs has been discovered to measure the ‘extent of risk’ with regard to crisp scores. Lastly, a reasonable structure for classifying risk factors into various risk levels has been built based on differentiated ranges of assessed crisp risk scores. Then, an activity necessity plan has been proposed, which could give direction to the officials for effectively controlling risk factors in the circumstance of orthopedic hospital.